Enhancing Academic Supervision with Digital Solutions: A Practical Evaluation of a Teacher Performance App in Madrasah - Asri, Nurfadila; Sahraini, Sahraini; Salmilah, Salmilah (Journal of Educational Management Research, 2025)
This study aims to describe the design and assess the level of practicality of using a teacher performance assessment application in madrasas as a digital solution that can improve efficiency, objectivity, and transparency in the academic supervision process. The approach used in this study is a quantitative descriptive method with an evaluative component, where data are collected through observation, documentation, and the distribution of questionnaires. The application consists of four integrated dashboards, specifically designed for principals, assessors, teachers, and students. Each dashboard is designed according to the function of its users, such as setting supervision schedules, filling out digital assessment sheets, uploading documents, and evaluating the learning process by students. The results of the practicality test showed a level of practicality of 95% for principals, 98% for assessors, 98% for teachers, and 97% for students, all of which are in the “very practical” category. These findings indicate that this application is practical and easy to implement in the madrasah school environment. This study provides implications that the use of teacher performance assessment applications can improve efficiency and transparency in the academic supervision process in madrasas. In addition, this application also encourages fairness and equality in teacher performance evaluation, which can ultimately contribute to improving the quality of education in madrasas.